Mitigasi Bencana untuk Daerah Rawan Longsor - Dhi Bramasta; Sriyanto (Proceedings Series on Social Sciences & Humanities, 2021)
Natural disasters are natural occurrences that have an impact on the environment, which can be in the form of damage, causing casualties, loss of property, damage to infrastructure and life facilities and infrastructure. Avalancheor often called ground movement is an event geology that happens because of the movement of the masses rock or soil with various types and types such as falling rocks or large lumps of soil. In general, there are two factors that can cause landslides, namely driving factors and triggering factors. Driving factors are factors that influence the condition of the material itself, while trigger factors are factors that cause the movement of the material. However, the main cause is gravity which affects a steep slope, but there are other factors that trigger it. Indonesia is located on the three main plates of the world, namely the Pacific, Australian and Eurasian plates which cause Indonesia to experience frequent disasters. In addition, Indonesia is geomorphologically a country that has a complete land form. Starting from mountains, slopes, savanna, marine or coastal areas. Diverse topography and land use change will be one of the causes of landslides. Various topographical conditions and the many different land functions that occur in Indonesia are one of the factors causing landslides, so knowledge of landslide disaster mitigation in landslide-prone areas is absolutely necessary to realize disaster preparedness, namely to reduce losses and casualties due to disasters. This can be done in three stages, namely before a landslide disaster occurs, during a landslide disaster and after a landslide disaster occurs. Hence, knowledge of landslide disaster mitigation in landslide-prone areas is absolutely necessary to realize disaster preparedness, namely to reduce losses and casualties due to disasters. This can be done in three stages, namely before a landslide disaster occurs, during a landslide disaster and after a landslide disaster occurs. Hence, knowledge of landslide disaster mitigation in landslide-prone areas is absolutely necessary to realize disaster preparedness, namely to reduce losses and casualties due to disasters. This can be done in three stages, namely before a landslide disaster occurs, during a landslide disaster and after a landslide disaster occurs.